Pelatihan Cara Penghitungan Harga Pokok Produksi Pupuk Limbah Kulit Nenas - Suci Ramadhani; Kiki Joesyiana; Asepma Hygi Prihastuti; Suci Ramadhani; Sri Wahyuni; Sarli Rahman (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2021)
This study aims to determine how a company calculates the cost of goods manufactured. The prickly pineapple business group still has difficulty in classifying raw material costs, labor costs and factory overhead costs. This research uses descriptive qualitative method. Prior to the training, only 2 participants answered correctly about costs, 4 participants answered correctly about raw materials, 3 participants answered correctly about labor costs, and 5 participants correctly answered about factory overhead costs. The results of this study explain that in the early stages prior to the provision of training on how to calculate the cost of production, many participants did not understand about cost calculations and how to classify them. After the training, the participants of the prickly pineapple business group began to understand that after a briefing was held on how to calculate the cost of production, participants were able to classify the related costs into the calculation of the cost of products, and participants were also able to calculate financial statements for the business they were doing.